Equine urticaria: a clinical guide to management. Issue 6 (16th June 2014) - Diesel, Alison
Abstract : Urticaria (hives) is a fairly common clinical reaction pattern in horses. Although often attributed to allergic causes, several other aetiologies can lead to the manifestation of the condition. A thorough and complete history, specifically as it relates to dermatological disease, is the practitioner's most powerful tool in successful diagnosis and management. Advanced diagnostics such as allergen‐specific immunoglobulin E serum or intradermal allergen tests are only helpful when an allergic aetiology has been confirmed based on appropriate history. This article discusses the various causes and appearances of urticaria in the horse, and aims to help guide the practitioner in determining when additional diagnostics and therapeutics are indicated.